Simultaneous presentation of sarcoidosis and acute myeloid leukaemia: predisposition to pulmonary haemorrhage. Issue 7 (July 1994) - Williams, B; Francis, A; Durrant, S
Abstract : A case of coexistent acute myeloid leukaemia and sarcoidosis is reported. This was complicated by recurrent pulmonary haemorrhage during reinduction and consolidation chemotherapy. A review of published papers on malignancy and sarcoidosis, in particular acute leukaemia is given. The outcome of most cases of acute leukaemia and sarcoidosis is poor with respiratory complications a frequent cause of death in this group. It is proposed that modifications to treatment to avoid pulmonary toxicity and maintenance of platelet counts above 40 x 10(9)/l are warranted to reduce the risk of this complication.